2012
DOI: 10.1038/nature10823
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for iron piracy by pathogenic Neisseria

Abstract: SUMMARYNeisseria are obligate human pathogens causing bacterial meningitis, septicemia, and gonorrhea. Neisseria require iron for survival and can extract it directly from human transferrin for transport across the outer membrane. The transport system consists of TbpA, an integral outer membrane protein, and TbpB, a co-receptor attached to the cell surface; both proteins are potentially important vaccine and therapeutic targets. Two key questions driving Neisseria research are: 1) how human transferrin is spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
243
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(254 citation statements)
references
References 50 publications
11
243
0
Order By: Relevance
“…Increase in invasion rate (i.e., shift from carrier to infected status) due to high dust loads and persistent low humidity damaging immune defenses in the mouth and easing bacterial invasion [117] Higher transmission levels due to changes in living habits, such as proximity of individuals taking refuge from dusty winds [116] Co-occurrence of viral respiratory infections weakening the immune system and easing transmission and invasion by bacteria [118] Neisseria bacteria, responsible for meningitis, require iron-rich dust to grow and become virulent [119] In the case of meningitis in West Africa, the need for more research and a better understanding of precisely how major outbreaks are linked to dust haze from the Sahara is clear. This gap is being addressed by the Meningitis Environmental Risk Information Technologies (MERIT) project, an effort supported by several international organizations including WHO, WMO and the intergovernmental Group on Earth Observations (GEO).…”
Section: Hypothesis Referencementioning
confidence: 99%
“…Increase in invasion rate (i.e., shift from carrier to infected status) due to high dust loads and persistent low humidity damaging immune defenses in the mouth and easing bacterial invasion [117] Higher transmission levels due to changes in living habits, such as proximity of individuals taking refuge from dusty winds [116] Co-occurrence of viral respiratory infections weakening the immune system and easing transmission and invasion by bacteria [118] Neisseria bacteria, responsible for meningitis, require iron-rich dust to grow and become virulent [119] In the case of meningitis in West Africa, the need for more research and a better understanding of precisely how major outbreaks are linked to dust haze from the Sahara is clear. This gap is being addressed by the Meningitis Environmental Risk Information Technologies (MERIT) project, an effort supported by several international organizations including WHO, WMO and the intergovernmental Group on Earth Observations (GEO).…”
Section: Hypothesis Referencementioning
confidence: 99%
“…However, infection in these animals does not lead to extensive infection or to rash development 12,13 . Other animal models that have been described for the bacteremia aspect of Neisseria infection take into account the bacterial preference for human transferrin as an iron source 14,15 . Either supplementing human transferrin or expressing it from a transgene results in an increased bacterial load in the blood stream over an extended time period, but this model shows no bacterial adhesion or rash development 16,17 .…”
mentioning
confidence: 99%
“…The metal binding sites are located deep at these clefts in the N-and C-lobes, and the metal binding sites of these lobes are expressed as N-and C-sites, respectively. Crystallographic studies on Fe(III) 2 human serum-Tf, 2) Fe(III) 2 human Lf, 3) and Fe(III) 2 ovo-Tf 4) have demonstrated that the iron coordination is similar for these proteins, with the metal bound to four protein ligands (two Tyr, one Asp, and one His) and a CO 3 2− (bidentate) anion, and that the coordination geometries of the two specific sites in each protein are essentially equivalent. However, Harris 5,6) reported that the metal binding constants of various metal ions at the C-and N-sites are different and that the metal binding constant at the C-site is generally much larger than that of the N-site.…”
Section: Flexibility Of the Coordination Geometry At The N-site Of Cumentioning
confidence: 99%